Analysis and determination for the parameters of "cohesive element" in numerical model of single fiber composites, II: The strength parameters. (December 2015) - Wang, Xiaohong; Liu, Changxi; Tang, Zhanwen; Wen, Lihua; Bi, Fengyang; Sun, Xinyang
In this study, the micro-droplet debonding test for three kinds of different single fiber composites (CCF/epoxy resin-128, CCF/epoxy resin-5228, and CCF/ bismaleimide resin-5428) is carried out. Then the corresponding numerical model for the test is established in the general finite element software ABAQUS and the process of the elastic load transferring in the test is simulated. Based on the numerical results, the reasonable critical debonding load " F " in the test is analyzed and is extracted from the scattered experimental datum. And it is used to combine with the numerical simulation for the "interphase" debonding process in the test. So the strength parameters of the "cohesive element" in the numerical are analyzed and determined. It turned out that in the numerical model for the CCF/Bismaleimide5428 single fiber composite, the strength parameter of the "cohesive element" is much higher (they are 130 MPa). It is demonstrated that the strength of the "interphase" in this single fiber composite is much stronger than that in the other two single fiber composites. These parameters can also be used to characterize the properties of "interphase" in composites.